Growth patterns in a cohort of very low birth weight infants in Johannesburg: a retrospective review - Mackay, Cheryl Anne (My University, 2010)
INTRODUCTION: Improved survival of VLBW infants is raising several management issues. An example is that of growth and growth monitoring. AIM OF THE STUDY: To assess the growth of a cohort of VLBW infants born at CMJAH from term CGA to 20 months CGA. METHODS: A retrospective chart review was conducted on 139 VLBW infants (birth weight ≤ 1500g) born at CMJAH between 1 July 2006 and 28 February 2007. RESULTS: Comparison with a term growth reference showed initial growth failure followed by gradual catch up growth but with persistent deficits in length for age. Comparison with international VLBW references showed similar growth for weight and head circumference for age but with deficits in length for age. Growth parameters of the study sample were similar to those of other South African VLBW infants. CONCLUSION: Growth and growth monitoring in VLBW infants is complicated by characteristic growth patterns, high associated morbidity, controversies surrounding ideal growth and lack of an ideal growth reference. Significant deficits in length for age in the study sample may have been due to the large proportion of infants born SGA and the high prevalence of stunting in South African children. Current recommendations for growth monitoring of VLBW infants include the use of a VLBW reference up to two years CGA followed by a term growth reference thereafter
Thesis MMed (Paediatrics), Faculty of Health Sciences, University of the Witwatersrand
Keywords: low birth weight; growth